An Extensive Reflection on the First 5 Years of the Asian Journal of Agriculture and Rural Development (2018-2022) - Pandey, Pallavi; Sharma, Avichal (Journal of Data Science, Informetrics, and Citation Studies)
The Asian Journal of Agriculture and Rural Development (AJARD) marked its first publication in the year 2018, and this article examines the journal's evolution after being indexed in Scopus for the first time. The core purpose behind the conduct of this study is offering a bibliometric evaluation of this journal by cataloguing its citations, influential authors, most frequently used keywords, and geographical concentration of articles. To discover hot and relevant journal topics, we use co-occurrence analysis and keyword analysis in the timeline view. In light of the aforementioned research, we also address the problems faced by the journal. Academicians, researchers and stakeholders associated and interested in the matters pertaining to the economy and business will find this report useful in charting the development of this very journal. Quantitative and qualitative bibliometric data were analyzed using descriptive and graphic approaches. The authors accessed the journal's bibliometric data from Scopus, the biggest interdisciplinary database in the social sciences, using the VoSViewer software and Advanced Excel. To begin, we gauge the quality of our publications and citations using established bibliometric metrics. Secondly, we provide a compilation of the leading countries, regions, and institutions that have made contributions. In the next section, we demonstrate the analytical potential of the VOSViewer in the context of cartography. Co-authorship and co-citation networks facilitate the discovery of previously unsuspected relationships. The majority of the journal's 173 authors have ties to Nigeria's Delta State University. The journal is published in the United States by the Asian Economic and Social Society. One of the most promising publications in the fields of social science, agriculture, and rural development is the AJARD In such a short amount of time, authors from Nigeria have submitted 30 publications to the AJARD The next two most common contributors are from Indonesia and India, respectively. Agricultural and social science topics predominate in the articles published in the Journal of Rural Development. Articles are by far the most common sort of submitted content. So, new agricultural and social science developments in rural areas can be covered in the AJARD. This will be useful for the governments of developing countries with a large rural population and an agricultural economy in making informed decisions during this time of transition. The longevity of the Journal can be attributed to its editors, authors, and reviewers. This, as the authors themselves claim, is the first bibliometric analysis of this journal using Scopus-based papers with regard to the AJARD In this article, writers have examined bibliometric data, highlight historical patterns, and probe into the journal's potential future directions.
Keywords: Asian Journal of Agriculture and Rural Development; AJARD; Scopus; Asian J. Agric. Rural Dev.; Bibliometric analysis; Co-occurrence analysis; Social-sciences; Agriculture.